If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 4x + 5x = -92 Combine like terms: 4x + 5x = 9x 7 + 9x = -92 Solving 7 + 9x = -92 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9x = -92 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = -92 + -7 9x = -92 + -7 Combine like terms: -92 + -7 = -99 9x = -99 Divide each side by '9'. x = -11 Simplifying x = -11
| -5(b+4)-6b=24 | | 1+3n-4n=3n-11 | | 28000+3000n=36000+2000n | | 4x^2y^2+12xy+9= | | 2x+4=10x-36 | | -9-7b=8b-7 | | 1+c/8=c/4 | | 4x^2y^2+12xy+9=0 | | -5(m+9)-4+8m= | | 6+4q=7+3g | | 1/6-2/3x=1/12 | | 5x+4-7x=8+2x | | 7/12x9 | | 16n=432 | | -7y-1=6y-6 | | 5x-8=30x+7 | | -7x+3=2x+-1 | | 9r+2=65 | | -31-(-8.6)= | | 18-3.8t=7.36-1.96 | | 5(2x+5)=-35+30 | | 6m-1=5m-2 | | 2a+b=15.7 | | 18-3.8t=7.36-1.98 | | -3-4x=-5x | | (2k-4)x+(4k+6)y+(3q-2)=0 | | 3x-2.8=4.2-4x | | 9x+6x+4=114 | | 37=5 | | (2k-x)x+(4k+6)y+(3q-2)=0 | | 15.3-(-11)= | | 4(x-8)+x=26 |